PENGARUH PEMBIAYAAN MURABAHAH TERHADAP KESEJAHTERAAN EKONOMI ANGGOTA DI KOPERASI LKMS-A GAPOKTAN PANAMPUANG PRIMA KABUPATEN AGAM - Ratu Hazira; Novera Martilova (Jurnal Ekonomi dan Bisnis, 2023)
This study aims to determine the effect of munabahah financing on the economic welfare of members in the Koperasi LKMS-A Gapoktan Panampuang Prima Kabupaten Agam. The research method used is a quantitative method, the population in this study is customers who use cheap financing at the Koperasi LKMS-A Gapoktan Panampuang Prima Kabupaten Agam, the research technique used in sampling in this study is a simple random sample using the Slovin formula so that the sample used in research as many as 69 respondents. This study used research instrument tests, classical assumption tests, simple linear regression analysis techniques and to test the hypothesis used the coefficient of determination test (R) and partial test or test (t). Data research instruments used questionnaires with a scale that had been tested and met the requirements. validity and reliability. The results obtained from this study indicate that murabahah financing variables have a significant influence on the economic welfare of members with a t count > t table = 5.090 1.996. Based on the significance value of the output of SPSS 26.0 with a significance value of 0.000 > 0.05. the coefficient of determination (R square) is 27.9%, which can be said that the effect of variable X on variable Y is weak and the contribution is small, while the remaining 72.1% is influenced by other variables not included in this study. Other variables are infrastructure, use of technology, access to government assistance and location of residence.